The right to inherit from the landholders in the agricultural spectrum - Montoya-Dávila, Filiberto (Universidad Autónoma de Tamaulipas, 2011)
In the mexican agrarian law the institution of landholders has lacked legal basis as to their rights, because they exist in fact and are not contained in any consistent legal regulation, since the appearance of the estate is limited, it is intended by this work to clarify this issue and determine if it needs their full ordinary law regulation on the right to inherit, or if there was an omission by the legislator at the time that it was considered in the proposed reform of Article 27 of the Constitution; all situations that lead to place the squatters as a component of the rural sector devoid of social justice.